DIMENSI WAKTU DALAM ANALISIS TIME VALUE OF MONEY DAN ECONOMIC VALUE OF TIME - Yudiana, Fetria Eka (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2013)
The development of the Islamic finance theory today has become a hot issuediscussed, such as polemic of the concept of time value of money. This concept cored that money today is more valuable than the same amount of money in the future, so that the grounding or assumptions used by this theory is al ghunmu bila ghurmin (get results regardless of risk) and al kharaj bila dhaman (get results without issuing a charge), and it’s contrary to the principles of Islam. Then The positive time preference concept was replaced with the concept of economic value of time, this concept cored that time has economic value, not money has a time value